Cystoid Macular Edema Following Cataract Surgery with Low-Energy Femtosecond Laser versus Conventional Phacoemulsification - Van Nuffel S; Claeys MF; Claeys MH (Clinical Ophthalmology, 2020)
Stefaan Van Nuffel,1,* Matthias F Claeys,1,* Marnix H Claeys2 1Department of Ophthalmology, University Hospital Ghent, Ghent, Belgium; 2Okulus Eye Clinic, Kortrijk, Belgium*These authors contributed equally to this workCorrespondence: Stefaan Van Nuffel Email stefaan.vannuffel@hotmail.comPurpose: To compare postoperative changes in central subfield macular thickness (CSMT) and prevalence of cystoid macular edema (CME) in patients undergoing cataract surgery with low-energy femtosecond laser versus standard phacoemulsification.Design: This was a retrospective comparative real-world study.Methods: Postoperative data of 252 eyes of 165 patients were collected: 138 eyes received low-energy femtosecond laser-assisted cataract surgery (FLACS) and 114 eyes underwent conventional phacoemulsification cataract surgery (CPCS). Postoperative changes in CSMT and prevalence of CME were compared between the two groups.Results: There was a significant increase in mean CSMT from preoperative to postoperative values at 2.5 months in both the FLACS and CPCS group (p< 0.001). Mean change (preoperation to 2.5 months postoperation) in CSMT was 6.2± 11.5 μm in the FLACS group and 7.3± 26.6 μm in the CPCS group, which was statistically significant but clinically not relevant. Comparison of mean changes in CSMT (preoperation to 2.5 months postoperation) between the FLACS and CPCS groups revealed no significant differences. The rate of pseudophakic CME (PCME) development was lower in the FLACS group (1.4%) than the CPCS group (4.4%; p=0.247). When using PREMED criteria to define clinically significant PCME, only 0.7% patients in the FLACS group and 1.8% in the CPCS group showed development of clinically significant PCME (p=0.586).Conclusion: The mean change in CSMT and occurrence of postoperative CME was lower in the low-energy FLACS group than the standard-phacoemulsification group; however, the difference was not statistically significant.Keywords: cystoid macular edema, low-energy femtosecond laser, femtosecond laser-assisted cataract surgery, phacoemulsification cataract surgery